Discrete material optimization of composite structures subjected to initial excitation for minimum residual vibration - Niu, Bin; Feng, Ning; Lund, Erik; Leng, Yue (Thin-walled structures, 2022)
This work studies design optimization of laminated structures subjected to initial excitation for minimum residual vibration. The Discrete Material Optimization (DMO) method with solid isotropic material with penalization (SIMP) model is employed to perform the design optimization of stacking sequence, fiber angles, and selection of material for the composite structures. The transient vibration analysis of the composite structures excited by initial excitation can be performed via the finite element method, where the residual vibration is identified. The integration of squared displacement of residual vibration can be selected as the objective function, which can be greatly simplified by Lyapunov equation to reduce the computational time. A modal reduction method is employed to further improve the computational efficiency of vibration analysis. Since many linear constraints are included in the optimization formulation for discrete material optimization, sequential linear programming (SLP) algorithm with a trust region approach is used to conduct the optimization iteration with the help of the design sensitivities obtained by an adjoint method. Numerical examples are presented to illustrate the effectiveness of the proposed method. The influences of the distribution and magnitude of several initial excitations on the optimized solutions are discussed. •A design approach for composite structures with initial excitation is presented.•Minimization of residual vibration is realized for composite structures.•Analysis of residual vibration is simplified by Lyapunov equation.•Simultaneous design of stacking sequences, fiber angles and material is achieved.•Optimization of composite structures with many linear constraints is solved.